Towards Cognitive Cities Advances in Cognitive Computing and its Application to the Governance of Large Urban Systems - Portmann, Edy.; Finger, Matthias; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book introduces the readers to the new concept of cognitive cities. It demonstrates why cities need to become cognitive and why therefore a concept of cognitive city is needed. It highlights the main building blocks of cognitive cities and illustrates the concept by various cases. Following a concise introductory chapter the book features nine chapters illustrating various aspects and dimensions of cognitive cities. The logic of its structure proceeds from more general considerations to more specific illustrations. All chapters offer a comprehensive view of the different research endeavours about cognitive cities and will help pave the way for this new and innovative approach to governing cities in the future. .
Foreword -- What are Cognitive Cities? -- From Smart to Cognitive: A Roadmap for the Adoption of Technology in Cities -- Maturity Model for Cognitive Cities: Three Case Studies -- Cognitive Cities, Big Data and Citizen Participation: The Essentials of Privacy and Security -- Towards the Improvement of Citizen Communication through Computational Intelligence -- Digital Personal Assistant for Cognitive Cities: A Paper Prototype -- Verbalization of Dependencies Between Concepts Built Through Fuzzy Cognitive Maps -- Cognitive Cities: The Nairobi Case -- Innovative Urban Governance: A Game Oriented Approach to Influencing Energy Behavior -- Diversity Measures for Smart Cities.
Keywords: Computational intelligence; Sociology, Urban; Engineering design; Sustainability; Urban economics; Computational Intelligence; Urban Sociology; Engineering Design; Sustainability; Urban Economics